Meningkatkan Kemampuan Motorik Halus Anak Melalui Kegiatan Melukis dengan Berbagai Media pada Kelompok A TK Mardisiwi II Tuksongo - Mutiyem Mutiyem (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2021)
This study aims to improve fine motor skills through painting activities in group A TK Mardisiwi II Tuksongo, Pringsurat District. This type of research is classroom action research. The research subjects were 25 children of group A TK Mardisiwi II Tuksongo, Pringsurat District, consisting of 12 boys and 13 girls. The research was carried out in August s.d. October 2018/2019 school year. Data collection techniques using observation sheets and observation tools in the form of photos. Data analysis used qualitative and quantitative data analysis. The results showed that through painting activities with various media can improve the fine motor skills of early childhood. In the first cycle of the first meeting with the BSH criteria there were 3 children if the percentage was 12%, the MB criteria were 12 children or 48%, while the BB criteria were 10 children with a percentage of 40%. At the second meeting of the BSH criteria there were 13 children or about 52%, the MB criteria were 12 children or 48%, and there were no more children with BB criteria. In Cycle II, the first meeting with the BSH criteria was 21 children if the percentage was 84%, the MB criteria were 4 children or 16%, while the BB criteria were not there.